ANALISIS KINERJA KOPERASI KREDIT DI BANDAR LAMPUNG - Agnes Susana Merry Purwati (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2016)
Target of this research is to analyse channeling of credit to co-operation performance andanalyse credit risk to co-operation performance at Co-Operation Credit (KOPDIT) in BandarLampung. In executing this research of writer use descriptive method with approach of survey,(KOPDIT) in Bandar Lampung and credit risk have an effect on and negativity of signifikan to cooperation performance at Co-Operation Credit (KOPDIT)Its implication of influence of channeling of credit risk and credit to co-operation performanceis the importance of make-up of attention at member background/co-operation member candidate toconduct loaning and the importance of assessment of character/nature of from lender candidateconducted well and correctness.